Överlåtelse av upphovsrätt till datorprogram genom ett inkråmsförvärv - Särskilt om programmets källkod och felansvaret vid s.k. copyleft-smitta - Bergqvist,Sara (2017)
This paper examines the possibility of a complete and final transfer of copyright to a computer software through an acquisition of assets in a company. Furthermore, it is examined whether it is possible to qualify the transfer as a purchase according to The Sale of Goods Act (1990:931). The question of whether the transfer should be regarded as a purchase in accordance with The Sale of Goods Act, serves as a purpose for investigating the possibility to determine the software as a faulty good. It is also important for the question of liability in such event. This study particularly aims to investigate how the presence of open source code in proprietary source code can result in the software being considered as a faulty good. This is especially highlighted through an acquistion of assets in a company, since such a transfer could possibly result in distribution in a sense which activates the terms in GNU GPL for the entire source code. An acquistion of assets is helpful to describe the process of the transfer and highlight the risks for both parties. When an employee creates a computer program, the copyright, in its entirety, is transferred to the employer in accordance with 40 a § in the Act on Copyright in Literary and Artistic Works (1960:729). There is a principle stating that the parties must specify what parts of the copyright they intend to transfer, should the company thereafter transfer the copyright to another party. In court, the principle is applied next to general principles of contracts. The Sale of Goods Act is generally considered applicable for complete and final transfers of intellectual property. The source code is protected as a literary work in accordance with 1 § in the Copyright Act (1960:29). The source code can either be considered proprietary, and thereby a trade secret, or open, and thereby free to distribute. Copyright is used as a means to make the licensees of GNU GPL redistribute the modifications they make. Since the concept of copyleft makes the source code available to all licensees, it can be problematic if the use of open source code is unintentional. Finally, the study aims to assess whether The Sale of Goods Act constitutes an appropriate regulation of the liability for a faulty software, when open source code has been incorporated into the proprietary source code. There is no precedent ruling about the specific issue at hand, neither does the preparatory work for The Sale of Goods Act or the Copyright Act reveal a clear answer. In legal doctrine, intellectual property in general is examined and in some cases patents also. The existing material about faulty software concerns delivery from an outside party, which is relevant to the issue at hand. Thus, the answers are sought in doctrine, which appears to be fragmented. There is no uniform answer to whether The Sale of Goods Act states an appropriate regulation between the parties for when there is no agreement to determine when the good should be considered as faulty. However, the author finds that, considering the proposals in doctrine, a reasonable balance ought to be achieved if there is no strict liability. There ought to be a consideration of the circumstances in the particular case. The assessment can be based upon the buyer’s expectations about actual utilization, legal exploitation and protection against competition. The buyer’s expectation is presented a reasonable guideline in determining the liability. That is, when there is neither an agreement nor a fixed standard for determining whether the software is faulty.
Keywords: avtalsrätt; civilrätt; förmögenhetsrätt; immaterialrätt; IT-rätt; upphovsrätt; datorprogram; överlåtelse; företagsförvärv; källkod; öppen källkod; open source; proprietär källkod; copyleft; GNU GPL